Horizontal Web Reinforcement Configuration Analysis of Deep Beam Capacity and Behavior using Finite Element Modeling - Pranata, A. Y.; Tjitradi, D.; Prasetia, I. (Engineering, Technology & Applied Science Research, 2020)
A deep beam is a beam with a small ratio of its shear span to its effective depth. Deep beams at failure under shear mechanism behave as brittle in contrast to the normal beams which become ductile under the flexural mechanism. The shear failure of deeps beams can be prevented by providing a sufficient amount of web shear reinforcements. Providing horizontal web reinforcement to the RC deep beams is a way to increase their capacity to shear. Testing of the studied deep beams was performed by Finite Element Method (FEM) modeling with the aid of ANSYS software. To obtain valid parameters for modeling RC deep beams in FEM modeling, calibrating test have to be done through verification and validation processes. The study results of all studied RC deep beams show that by closing up the spacing between the horizontal web reinforcement results in increment in the ultimate load, while the ultimate deflection and the curvature ductility were found to be decreasing. For RC deep beams, the placing configuration of horizontal web reinforcement at 0.5h-0.7h was found to be efficient for gaining higher values of ultimate deflection and curvature ductility compared to the placing configuration at 0.3h-0.5h with similar values of ultimate load. It was also found that all the specimens’ crack patterns at the first crack state were caused by flexural-tension while at the ultimate state, they were caused by the shear mechanism.